2020
DOI: 10.1002/ehf2.12547
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril‐Valsartan in a routine community population: attention to volume status critical to achieving target dose

Abstract: Aims In the PARADIGM‐heart failure trial, sacubitril‐valsartan demonstrated a reduction in heart failure admissions and reduced all‐cause mortality in patients with heart failure with reduced ejection fraction. Although real world data have shown similar benefits regarding efficacy and safety, there has been difficulty in achieving the target dose (TD). The factors preventing the achievement of TD remains unclear. This study assesses the tolerability, ability to achieve, and factors linked to attaining TD in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 30 publications
7
36
3
1
Order By: Relevance
“… 12 Similarly, a more recent retrospective study in patients with HFrEF showed that the target dose of sacubitril/valsartan 97/103 mg was achieved in 65.3% of the total assessed population of 322 patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Similarly, a more recent retrospective study in patients with HFrEF showed that the target dose of sacubitril/valsartan 97/103 mg was achieved in 65.3% of the total assessed population of 322 patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“…For example: the average age of a patient with heart failure in the UK is 77 years at diagnosis, 87 whereas the average age of a patient in PARADIGM-HF was over 10 years younger. 4 However, data from real-world populations suggest that treatment with sacubitril-valsartan is associated with significant reductions in NTproBNP, 88 increases in LVEF, 88 and reductions in the rate of heart failure hospitalisation compared to pre-initiation. 89,90 The ARIADNE registry, which aims to describe current prescribing trends with regards to sacubitril-valsartan, is recruiting and will highlight any discrepancies.…”
Section: Real-world Data and Future Perspectivesmentioning
confidence: 99%
“…[ 50 , 51 ] The benefits in terms of prognosis, rehospitalisation and quality of life offered by ARNI suggest that therapy initiated at the maximum tolerated dose, during the HFrEF stage, has to be continued at the same dosage, and should be down-titrated only if acute kidney failure or severe hypotension occur. [ 52 , 53 ] In the Efficacy and Safety of LCZ696 Compared to Valsartan, on Morbidity and Mortality in Heart Failure Patients With Preserved Ejection Fraction (PARAGON-HF) trial, ARNI failed to reduce the primary composite endpoint of total hospitalisations for HF and CV death in patients with HF and LVEF ≥45%. [ 54 ] However, when data from Efficacy and Safety of LCZ696 Compared to Enalapril on Morbidity and Mortality of Patients With Chronic Heart Failure (PARADIGM-HF; eligibility criterion LVEF ≤40%; n=8,399) and PARAGON-HF (eligibility criterion LVEF ≥45%; n=4,796) were combined in a prespecified pooled analysis, the therapeutic effects of sacubitril/valsartan (ARNI) compared with a renin–angiotensin system inhibitor alone varied according to LVEF, but treatment benefits, particularly for heart failure hospitalisations, appeared to extend to patients with HFmrEF.…”
Section: Predictors Of Lvef Transitionmentioning
confidence: 99%